Genomic Organization and Evolution of the Trace Amine-Associated Receptor (TAAR) Repertoire in Atlantic Salmon (Salmo salar). Issue 6 (1st June 2014) - Tessarolo, Jordan A; Tabesh, Mohammad J; Nesbitt, Michael; Davidson, William S
Abstract: There is strong evidence that olfaction plays a key role in the homing of salmonids to their natal spawning grounds, particularly in the freshwater phase. However, the physiological and genetic mechanisms behind this biological phenomenon are largely unknown. It has been shown that Pacific salmon respond to dissolved free amino acids from their natal streams. This indicates that amino acids comprise part of the olfcatory cues for imprinting and homing in salmonids. As trace amine-associated receptors (TAARs), a class of olfactory receptors that are close relatives of the G protein-coupled aminergic neurotransmitter receptors, recognize amino acid metabolites, we hypothesize that TAARs play an important role in salmon homing by recognizing olfactory cues. Therefore, to better understand homing in Atlantic salmon, we set out to characterize the TAAR genes in this species. We searched the first assembly of the Atlantic salmon genome for sequences resembling TAARs previously characterized in other teleosts. We identified 27 putatively functional TAAR genes and 25 putative TAAR pseudogenes, which cluster primarily on chromosome 21 (Ssa21). Phylogenetic analysis of TAAR amino acid sequences from 15 vertebrate species revealed the TAAR gene family arose after the divergence of jawed and jawless vertebrates. The TAARs group into three classes with salmon possessing class I and class III TAARs. Within each class, evolution is characterized by species-specific gene expansions, which is in contrast to what is observed in other olfactory receptor families ( e.g., OlfCs and oras).